A reforma da previdência social no Brasil durante os governos Collor/Itamar, FHC e Lula (1990-2003) - Leão, Patrícia Bonilha (2013)
The 1988 Constitution is the Constitutional Charter was instituted more social rights, among these are pension rights, both in relation to the General Welfare, the criteria governing the granting of retirement to workers whose contract of workers are governed by the Labor Code, as the Regime of Social Security Self, the civil servants and the military. Despite these advances in social rights were the result of struggles and demands of men and women who took to the streets in search of better conditions of work and life, organized into unions, leftist parties, social movements, the promulgation of the Charter was made by elite Brazil, represented by the right. However, barely closed the adoption of this Constitution, these same groups, began working in the implementation of capitalism in its neoliberal form, starting coupled to this process of "welfare reform Brazilian". Despite attempts to implement this throughout the Collor / Itamar, this was effective only in 1998 with the approval of Constitutional Amendment. 20/98. This amendment ended with retirement for length of service, deployed retirement contribution time, set maximum limit for payment of pension benefits under the general scheme and the mandatory pension scheme, following criteria set by the World Bank, the IMF and government linked U.S. However, even getting the approval of Amendment. 20, the Cardoso government failed to move towards deregulation pension rights of public employees. This setback was achieved in the reform implemented following the end of the 1st year of the Lula government (2003), through the adoption of Constitutional Amendment 41. Our goal is to analyze the process of pension reform in Brazil, 1990-2003, from the discussions in the polls of PECs in the National Congress, thought of as political society, formed by representatives of groups with heterogeneous interests, aiming to realize the contradictions and conflicts intra / extra-class